Application of the Data Envelopment Analysis Method to the Evaluation Information System of the Study Program at Politeknik Negeri Media Kreatif based on Web App - Suhendra Suhendra; Komda Saharja (STMIK Budi Darma, 2021)
Assessment of the performance of the Study Program is a routine activity carried out by the College to continuously improve the quality of its services. One form of assessment of the performance of the study program is the accreditation of the institution. Therefore, it is necessary to build a system that is able to perform automatic assessment of the performance of the study program. In performance assessments are often found the variables used are quantitative and / or qualitative. Data Envelopment Analysis (DEA) can be viewed as an aggregation operator for variables of quantitative and qualitative value. This Study Program performance assessment system uses the Data Envelopment Analysis (DEA) method and the software development method used, rad (rapid application development).This system produces an efficiency value of the level of performance of all Study Programs at the Politeknik Negeri Media Kreatif in general and the Graphic Design Study Program (Kampus Medan) in particular, whether it is optimal or not, if not then this system aims to provide material consideration of the value of variables / attributes that need to be reduced or added. The data obtained from these measurements can be used as an analysis of the situation of the next program. The way this application works is designed using the php programming language, and the CodeIgniter framework, on the database server section using MySQL